Drivers and Barriers of Carbon Footprint Reduction in the Hospitality Sector - Ngoni C. SHERENI; Christian M. ROGERSON (African journal of hospitality, tourism and leisure, 2024)
Business operations of hospitality enterprises are subject of intense scrutiny to determine how they are contributing to the climate action agenda. Existing scholarship is dominated by research conducted in the Global North. This paper contributes a Global South perspective and aims to identify the drivers and challenges for the adoption of carbon footprint strategies in the hospitality sector. The study randomly sampled 165 establishments from the hospitality sector in Zimbabwe. A structured questionnaire was used to collect data from the respondents and SPSS version 29 was used to generate descriptive and inferential statistics. The results reveal that the main drivers for carbon footprint reduction include a positive public image, conforming to industry best practices, as a Corporate Social Responsibility (CSR) initiative, reduction in operating costs and gaining competitive advantage. Identified barriers include financial constraints, high costs of procuring energy-efficient appliances, lack of knowledge, skills gap, weak legal framework and lack of industry cooperation. Arguably, policy interventions for the decarbonisation of hospitality enterprises must be country-specific and broadly seek out local interventions designed to increase pressures, lower barriers and boost incentives for climate change action.